2018
DOI: 10.1186/s40634-018-0161-5
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and reliability of knee goniometry methods

Abstract: BackgroundMeasuring knee range of motion is important in examination and as a post-operative outcome. It is therefore important that measurements are accurate. Knee angles can be measured by traditional goniometers, smartphone apps are readily available and there are also purpose made digital devices. Establishing the minimum difference between methods is essential to monitor change. The purpose of this study was to assess reliability and minimum significant difference of visual estimation, short and long arm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
106
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(126 citation statements)
references
References 10 publications
(24 reference statements)
3
106
1
2
Order By: Relevance
“…If we were to consider all the studies that assessed relative intra-rater reliability with an iPhone 4, all six studies demonstrated that smartphone apps had adequate relative intra-rater reliability [1, 34, 37, 42, 48, 64]. Thirteen of 17 studies reported good absolute intra-rater reliability as defined by a SEM or MDC < 5 o or LOA < ± 9.8 o for more than 50% of the joint movements they examined, with only four studies not satisfying this threshold [40, 44, 51, 59]. It should however be noted that the study by Quek et al [44] satisfied the criteria for more than 50% of the movements when quantified by the SEM (the three of the four movements) but failing this when reliability was assessed by the MDC for all four movements.…”
Section: Resultsmentioning
confidence: 99%
“…If we were to consider all the studies that assessed relative intra-rater reliability with an iPhone 4, all six studies demonstrated that smartphone apps had adequate relative intra-rater reliability [1, 34, 37, 42, 48, 64]. Thirteen of 17 studies reported good absolute intra-rater reliability as defined by a SEM or MDC < 5 o or LOA < ± 9.8 o for more than 50% of the joint movements they examined, with only four studies not satisfying this threshold [40, 44, 51, 59]. It should however be noted that the study by Quek et al [44] satisfied the criteria for more than 50% of the movements when quantified by the SEM (the three of the four movements) but failing this when reliability was assessed by the MDC for all four movements.…”
Section: Resultsmentioning
confidence: 99%
“…A universal goniometer was placed next to the femoral lateral epicondyle. The static handle of the goniometer was aligned with the thigh, using the femoral major trochanter as a reference, while the mobile handle aligned with the leg referencing the fibula lateral malleolus [ 31 ]. For the knee extension assessment, patients lay in a supine position and the limb being evaluated was raised by the heel, with knee stabilisation in contact with the stretcher.…”
Section: Methodsmentioning
confidence: 99%
“…In both regular care and clinical trials, the decrease that was seen shortly after KJD, recovered within months and normalized after a year, with the observed changes being minimal and less than the minimally detectable difference reported in literature. [27] As such, the differences are considered not to be clinically relevant and within variation of measurement.…”
Section: δWomac Mean (95%ci)mentioning
confidence: 99%